Optimization of Electrochemical Sensors and Their Application in CO2 Detection - Zhang, Hongyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In response to the increasing global greenhouse gas content, electrochemical sensors with the advantages of existing main detection methods have the problem of being very sensitive to temperature, and long-term exposure to greenhouse gases will seriously affect the service life. From the aspects of sensitivity, selectivity, internal structure and working principle, this research points out the research progress of existing electrochemical sensors for detecting carbon dioxide (CO2), which consist of ionic liquid base, solid polymer electrolyte, room temperature fluorinated anionic liquid and boric acid stable tungsten oxide solid electrolyte. It is also discussed that by optimizing the internal structure of the sensor and improving the composition of the sensor, the detection range and the applicable environment of the electrochemical sensor can be expanded, so as to reduce its sensitivity to temperature and finally achieve the result of prolonging its service life. On the basis of the research, the influence of different structures on the function of electrochemical sensor is discussed, the advantages of electrochemical sensor for CO2 detection are analyzed, and the future detection of carbon dioxide by electrochemical sensor is prospected.